Responsiveness in Supply Chains: Comparative Competitive Implications for Malaysia and Singapore - Vaz, Anthony; Kang Ni, Connie Chan (International Journal of Supply Chain Management, 2026)
In the dynamic and globalized logistics landscape, supply chain competitiveness increasingly hinges on responsiveness and punctuality. This study investigates how this critical speed dimensions contribute to competitive advantage in Malaysia and Singapore, two strategically located nations in Southeast Asia. Drawing on qualitative survey data from logistics professionals and the general population, the research examines the multifaceted causes of lateness and delays, encompassing individual behaviours, organizational practices, and systemic infrastructural factors. Findings reveal distinct cultural and operational differences influenced by Hofstede’s Long-Term vs. Short-Term Orientation framework, highlighting Singapore’s emphasis on discipline and future planning versus Malaysia’s flexible time management approach. The study underscores the necessity for integrated behavioural and structural interventions, such as improved communication, real-time updates, and organizational policy reforms, to enhance supply chain performance and customer satisfaction. By contextualizing supply chain speed beyond mere transportation velocity to include communication and decision-making efficiency, this research provides actionable insights for practitioners and policymakers aiming to bolster logistics effectiveness and regional competitiveness.